Spatial Variations in the Characteristics of Oscillated and Non-Oscillated Solar Bright Points in Active Regions and Coronal Holes - Rayhane Sadeghi; Ehsan Tavabi (Iranian Journal of Astronomy and Astrophysics)
In this study, researchers investigated the properties of oscillated and non-oscillated bright points (BPs) in different regions of the Sun, including active regions (ARs) and coronal holes (CHs). The findings revealed both differences and similarities among these BPs across the various regions. Firstly, the study observed that internetwork BPs in ARs exhibited higher damping times compared to network BPs. Additionally, internetwork BPs in ARs displayed wider ranges of maximum Doppler velocities in comparison to network BPs. Although both forms of BPs had comparable damping times, internetwork BPs demonstrated greater maximum Doppler velocities than network BPs. Moreover, the study provided insights into the damping behavior of BPs in different regions. Specifically, it was noted that the majority of network BPs in ARs exhibited overdamping, indicating that the damping effects were dominant. On the other hand, in CHs, internetwork BPs displayed overdamping behavior, suggesting a similar dominance of damping effects. In contrast, oscillated network BPs in CHs exhibited critical damping behavior, implying a balance between damping and driving forces. It is important to emphasize that the physical principles underlying BP damping may vary depending on the local plasma conditions and magnetic surroundings. Overall, this study highlights the diverse characteristics of BPs in different solar regions, shedding light on their damping times, maximum Doppler velocities, and damping behaviors. These findings contribute to our understanding of the intricate dynamics and plasma conditions occurring in different areas of the Sun, providing valuable insights into the complex nature of solar phenomena.